Social work and projects of society in Brazil - Behring, Elaine Rossetti (Critical Proposals in Social Work, 2021)
In this article we discuss the main projects of society disputed on the Brazilian scene. This analysis allows us to draw conclusions about the whole of Latin America and the world situation, discussing the expressions of social work, its challenges and conditions for the defence of the ethical-political project built by the Brazilian Social Service after the Virada Congress of 1979, forty-one years ago. At that time, we bravely held legitimate collective elections, which today are challenged by these times of reactionary tones, but also marked by struggles, resistance and contradictions. The strong winds that blow in several Latin American countries, especially in Chile, show us that “everything changes”, as the beautiful music of Julio Numhauser says, immortalized in the voice of the Argentine Mercedes Sosa. That is to say, nothing is and should not seem impossible to change. Therefore, we will focus on a more generalized characterization of these social projects, seeking to carry out some mediations with our professional project.